Relationship between electronic cigarettes and oral cancer: A literature review (Research, Society and Development, 2024)
The aim of this study is to establish the relationship between the use of electronic cigarettes and the incidence of oral cancer, evaluating the chemical components, biological mechanisms and associated toxic effects. A comprehensive review of the scientific literature was carried out, analyzing studies published between 2018 and 2024. The results indicate that electronic cigarette aerosols contain chemicals that can break down into toxic compounds such as formaldehyde and acetaldehyde, known carcinogens. These compounds, when inhaled, can induce cytotoxic and genotoxic effects in the cells of the oral cavity, generating DNA damage and increasing the risk of oral cancer. In addition, the alteration of the oral microbiome by the use of electronic cigarettes can favor the growth of pathogenic bacteria that are associated with periodontal diseases and caries, and that could contribute to the development of oral cancer through mechanisms of chronic inflammation and production of carcinogenic metabolites. We conclude that although e-cigarettes are presented as a less harmful alternative compared to traditional cigarettes, current findings indicate that they are not free from significant risks to oral health, highlighting the need for greater monitoring and regulation of their use.